Analysis of in-service composite insulators used in overhead railway traction. (January 2020) - Subba Reddy, B.; Ramamurthy, Praveen C.
Highlights: Experimental Investigations conducted on composite insulators used for overhead rail traction. Leakage current and surface resistance measurements are analyzed and presented. Surface morphological changes using SEM, FTIR, Hydrophobicity measurements reported. Investigations reveal low surface resistance and high leakage currents for field aged insulators. Abstract: Polymeric based Composite insulators are extensively used for overhead rail electric traction system; these insulators play an important role in the traction electrification which supply power to the locomotives of train. Traction insulators are subjected to a variety of stresses, like mechanical, electrical, environmental, etc., these stresses act in unison, degradation and subsequent failure of traction insulator influences the safety of traction power supply system. To understand the phenomena of degradation and in-service aging, experimental investigations are conducted on in service traction insulators to identify and analyze the structural changes occurred in the field for a specified time, the insulators are of composite silicone polymeric materials rated for 25 kV. The electrical performance on the insulator samples is investigated using leakage current analysis and surface resistance measurements under normal and fog/moisture conditions using a specifically designed fog test chamber. The structural changes are studied by using Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDAX), Fourier Transform Infra-Red (FTIR) and wettability measurements. The study highlights the in-depth analysis conducted on the performance of service insulators compares with the fresh, also suggests mitigation methods to overcome the probable failures in the field. Some interesting results obtained from the study are analyzed and presented.